Change in skeletal muscle mass is associated with lipid profiles in female rheumatoid arthritis patients -TOMORROW study-. Issue 6 (June 2021) - Matsumoto, Yoshinari; Sugioka, Yuko; Tada, Masahiro; Okano, Tadashi; Mamoto, Kenji; Inui, Kentaro; Habu, Daiki; Koike, Tatsuya
Summary: Background & aims: To examine the relationship between changes in skeletal muscle mass and lipid metabolism and glycometabolism in patients with rheumatoid arthritis (RA). Methods: Data were analyzed from 148 female RA patients and 145 age-matched non-RA (control) female subjects from a prospective cohort study (TOMORROW; TOtal Management Of Risk factors in Rheumatoid arthritis patients to lOWer morbidity and mortality study). Appendicular skeletal muscle mass (ASM) was assessed using dual-energy x-ray absorptiometry and skeletal muscle mass index (SMI) was calculated as ASM divided by the square of height. The reference value for SMI in Asian women, 5.4 kg/m 2, was used to define low SMI. Data were assessed using cross-sectional (2010 baseline data) and longitudinal (change in value from 2010 to 2013) methods from the retrospective cohort. Results: At baseline in RA patients, the low SMI group showed significantly higher low-density lipoprotein cholesterol (LDL-chol) ( p = 0.015), apolipoprotein (Apo)B ( p = 0.046), and ApoB-to-A1 (ApoB/A1) ( p = 0.025) than the normal SMI group. In multiple regression analysis of RA patients, sequential changes from 2010 to 2013 (Δ) in SMI and ApoB and ApoC2 showed significant negative relationships (β = −0.19, −0.18, respectively) even after adjusting for age, RA duration, exercise habits, medication for RA, disease severity, activities of daily living (ADL) and body fat mass. No significant relation was evident between ΔSMI and various glycometabolism parameters in RA patients. Conclusions: Skeletal muscle mass might be related to lipid metabolism in RA patients. This relationship is independent of factors such as disease severity and body fat mass.